PERUBAHAN-PERUBAHAN PENTING TERKAIT HAK CIPTA PASCA UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Sujana Donandi S (Problematika Hukum, 2015)
Act no. 28 Year 2014 is the latest regulation concerning copyright. Act no. 28 2014 is expected to brought important changes that could be useful in improving protection and law enforcement of copyright in Indonesia. This research focus on important changes related to copyright after act no. 28 2014 was legalized and its legal consequences. Method used in this research is normative legal research which specifically described changes related to copyright based on  Act no. 28 2014 .The results and discussion shows that Act no. 28 2014 brings important transformation of copyright such as: economic rights protection that more favors to the creator, more effective dispute settlement, copyright can be fiduciary security , and the emergence of Lembaga Managemen Kolektif.